Macrostructures and rhetorical moves in research articles in nanotechnology - Luo, Xianqing; Ji, Jiajie (Frontiers in Psychology, 2025)
IntroductionNotwithstanding the fact that extensive studies focused on exploring generic structures in established disciplines, scant attention has been directed to macrostructures and rhetorical moves in RAs in some emerging disciplines.MethodsBased on a self-compiled corpus of 50 research articles (RAs) from five top ranking journals in the field of Nanotechnology, we explored the macrostructures and rhetorical moves in RAs in Nanotechnology.ResultsIt was found that (i) scientists in Nanotechnology have a propensity to employ a merged [R&D] structure to immediately discuss and contribute new knowledge tentatively in the specific contextualised situation after research results were presented, (ii) Even though RAs in Nanotechnology largely follows IMRD structure by abiding writing conventions in the research world, disciplinary variations were found regarding the rhetorical structures, specifically, scientists in Nanotechnology tend to employ more moves and steps in establishing research niche, detailed description of research methods, suggesting future research, but less moves and steps related to promotional strategies (M3S4, M3S5, M3S6).DiscussionThe research results have significant implications for English for Academic Purposes (EAP) instructors to make informed choices by using disciplinary empirical-based decisions to guide novice writers and students at tertiary level to write RAs by following disciplinary conventions of research communities in Nanotechnology so as to avoid overgeneralization.